Pod Corn Is Caused by Rearrangement at the Tunicate1 Locus([W])([OA]) - Han, Jong-Jin (American Society of Plant Biologists, 2012)
Pod corn (Zea mays var tunicata) was once regarded as ancestral to cultivated maize, and was prized by pre-Columbian cultures for its magical properties. Tunicate1 (Tu1) is a dominant pod corn mutation in which kernels are completely enclosed in leaflike glumes. Here we show that Tu1 encodes a MADS box transcription factor expressed in leaves whose 5′ regulatory region is fused by a 1.8-Mb chromosomal inversion to the 3′ region of a gene expressed in the inflorescence. Both genes are further duplicated, accounting for classical derivative alleles isolated by recombination, and Tu1 transgenes interact with these derivative alleles in a dose-dependent manner. In young ear primordia, TU1 proteins are nuclearly localized in specific cells at the base of spikelet pair meristems. Tu1 branch determination defects resemble those in ramosa mutants, which encode regulatory proteins expressed in these same cells, accounting for synergism in double mutants discovered almost 100 years ago. The Tu1 rearrangement is not found in ancestral teosinte and arose after domestication of maize.